Implementation of Criminal Law in Handling Narcotics Cases in Indonesia - Bahtiyar Efendi; Widhi Handoko (Faculty of Law, Universitas Pekalongan, 2022)
The problem of narcotics is currently rife in Indonesia. The rise of drug cases is common among teenagers, especially. The territory of Indonesia is very strategic because of its extensive area with various small islands. Drug abuse is a criminal act because three things cause it: the first is applying criminal law, prevention without criminal punishment, and the last one that can make people's views of drug abuse users wrong. In regulating the abuse of drug use, the government has regulated it in Law No. 35 of 2009 concerning narcotics.Keyword :Criminal, Law, Narcotics, Indonesian Law